Strategi Peningkatan Kreativitas dan Motivasi Masyarakat Desa Jogomulyo Melalui Sosialisasi Kepemudaan - Arya Pramudya Manggala Putra; Aldilla Kurnia Eka Savita; Eka Febrianti; Muhammad Miftachul Rizki Al Bar; Sandra Audina Maharani; Sri Hastuti (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Kuliah Kerja Nyata (KKN) is a form and concrete action by carrying out community service. One of the community service activities carried out through socialisation activities on digital marketing and training on CV making and job application letters involving the surrounding community, especially the youth of Jogomulyo Village. This activity aims to increase the creativity and motivation of the Jogomulyo Village community through socialisation of youth sensitivity to the world of work. In the era of globalisation, qualified skills are very important to compete. Activities carried out by Tidar University students include socialisation of digital marketing and training in making Curriculum Vitae (CV) and job application letters. The method used was to socialise the Jogomulyo Village community by presenting material and interactive sessions between the speaker and the audience. The target participants were village youth who need to prepare themselves to enter the world of work more professionally and be better prepared to compete in the era of modernisation. The results of the activity showed an increase in participants' understanding of digital marketing and effective job application document preparation techniques. The evaluation showed the need for further training to improve participants' skills. Thus, this kind of activity can contribute to equipping the community with relevant knowledge and improve their competitiveness in the world of work.